STATE AND PROSPECTS OF FISH MARKET DEVELOPMENT IN UKRAINE - Волхова, Т.; Голембовская, Н. (SWorldJournal, 2021)
Catch and consumption of fish are increasing all over the world, which cannot be said about Ukraine, because the average annual consumption of fish and fish products is much lower than the world average. The fish market in Ukraine is represented primarily